Multidisciplinary top management teamwork: effects on local health department performance - Lovelace, K (Journal of public health management and practice, 2001)
Local health departments often use multidisciplinary top management teams (TMTs) to organize the work of the agency. The purpose of this study was to examine the use of TMTs in North Carolina local health departments and how TMTs use affected agency performance. TMT diversity and TMT performance positively affected the local health departments' (LHDs) performance. As well, the TMTs' agenda affected LHD performance. The more that TMTs discussed community health assessment and political changes in the community, the better the LHD performance on the core functions. Implications for public health practice and leadership in local health departments are discussed.